Hubungan Antara Pengetahuan tentang Keluarga Berencana dengan Keinginan Menjadi Akseptor pada Calon Pengantin Laki-Laki di Kota Surakarta - Fardianingtyas, Rifni Arneswari; Hanim, Diffah; Lestari, Anik (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background:Family planningis one of policy and strategy from government to handle demoghraphic problem in Indonesia. Based on the theory, knowledge is an important domain to form someone attitudes and the attitude can be formed based on knowledge is willingness. The objective of this study is to identify association between knowledge about family planning with the prospective groomâs willingness to be an acceptorin Surakarta. Methods:This study was an observasional analitic with cross sectional design. Seventy subjects from five Departement of Religion Office (KUA) in Surakarta fulfilled the inclution criteria, were selected by purposive sampling method.Knowledge about family planning and prospective groomâs willingness to be an acceptor were collected through a questionnaire. The association between knowledge about family planning with prospective groomâs willingness to be an acceptor were analyzed by Chi Square. The power of association between variables were analyzed by Contingency Coefficient. Results:There were, 8 subjects (11.4%) had good knowledge, 27 subjects (38.6%) had enough knowledge, and 35 subjects (50%) had less knowledge. Twenty two subjects (31.4%) wanted to be an acceptor in the future and forty eight subjects (68.6%) did not want to be an acceptor in the future. Chi square test revealed significant assosiciation between knowledge about family planning with prospective groomâs willingness to be an acceptor (p = 0.001). Conclusions: There wasassociation between knowledge about family planning with prospective groomâs willingness to be an acceptor in Surakarta. Keywords:Knowledege, Family Planning, AcceptorÂ